On dynamic analysis and damage evaluation for bridge girders under high-energy air burst. (July 2022) - Yang, Shanglin; Zhong, Wei; Wang, Shufei; Kong, Weiming; Tang, Ziqi; Tian, Zhou; Zhang, Run; Yao, Xiaohu
Abstract: This study aims to investigate the dynamic response and damage effect of bridge girders under high-energy air burst numerically. The numerical method adopted is validated against a blast experiment. A representative T-shaped girder prototype is selected based on a national specification and the refined model of it is established. Blast scenarios of an automobile explosion and three high-energy air bursts with different detonation heights are employed to explore the failure modes and dynamic response of the girder. Numerical results indicate that the damage is local for conventional chemical explosions, while the destruction is overall for high-energy air bursts. Based on the response characteristics of the girder, a normalized bearing capacity criterion and maximum deflection criterion are proposed. Compared with the original bearing capacity criterion, the normalized one provides a more in-depth description for the resistance of girders to high-energy air burst loads and the maximum deflection criterion improves the evaluation efficiency. A damage evaluating scheme incorporating damage criteria, damage levels and P-I curves is further developed. The damage regularities of the girder under high-energy air burst loads are obtained using the present scheme. The present research can provide a feasible solution for bridge anti-explosion analysis and damage assessment.